Legal Protection For Grab Drivers Due to Default Related to Double Order Payments on Grabfood Services By PT. Indonesian Technology Grab - Sri Maharani*; Gunawan Candra (Universitas Syiah Kuala, 2023)
The development of information technology forces conventional activities to be abandoned and people begin to switch to using information technology, like buying and selling food. GrabFood is a food delivery service provided by the GRAB application. the GrabFood service has a Double Orders. Double Orders funding is below what it should be, so that indicates a default on the agreement.The type of legal research used in this research is normative juridical. This research uses a statutory approach which is carried out by examining all laws and regulation. The data collection method used in this research is library research, papers, articles, the internet, research results, laws and regulations. The data analysis method uses a descriptive analytical research method. In the case of Double Orders on the GrabFood service, the GRAB Applicator has committed a default in the form of carrying out what has been promised but not as promised. Preventive legal remedies that GRAB drivers can take to fulfill rights that are not fully granted are by urging the government to immediately issue laws or regulations prohibiting system fraud which is detrimental to online motorcycle taxi drivers in general. The Partnership Agreement between the GRAB Driver and the GRAB Applicator explains that if a dispute occurs, it will be resolved through a non-litigation route, namely through arbitration.